CONSTRUCTION AND ANALYSIS OF THE ADVERTISING DISTRIBUTION MODEL - T.R. NIKITINA (Association of Social and Educational Innovation, 2023)
The study investigates the construction characteristics and evaluates the advertising distribution model by utilizing the case of beauty products as an example.